Efektivitas Media Pembelajaran Berbasis Augmented Reality Dalam Meningkatkan Motivasi Belajar IPA - Cindrianadinda (Jurnal Ilmu Pendidikan Biologi dan IPA, 2025)
This study aims to examine the effectiveness of Augmented Reality (AR)-based learning media in enhancing students’ motivation in Science (IPA) learning at the junior high school level. The research background lies in the low learning motivation of students, as Science is often perceived as abstract and difficult to understand. A quasi-experimental method with a Nonequivalent Control Group Design was employed, involving two eighth-grade classes as the experimental and control groups. The research instrument was a motivation questionnaire that had been tested for validity and reliability. Data analysis results revealed a significant increase in learning motivation among students in the experimental group using AR media compared to those in the control group taught through conventional methods, with a significance value of 0.000 < 0.05. These findings indicate that AR provides interactive, concrete, and immersive learning experiences, making it effective in stimulating students’ motivation. This study recommends the integration of AR-based media as an innovative strategy to improve the quality of Science learning in schools..